Establishment of Dams and Embankments of Frontier River of North East Part of India: Impact on North-Western Region of Bangladesh - Rahman, MM; Rahman, MR; Asaduzzaman, M (Journal of Science Foundation, 2013)
India has built barrages on 17 more rivers in the east and northeast border with Bangladesh. Most of these dams and embankments act as the main barrier to flow water towards downstream like Bangladesh. As a result the rivers of Bangladesh that comes from India are falling in crisis of proper water. A study showed about 30 rivers of north-western part of Bangladesh gets very few water only due to dams and embankment made by India at the upstream of those rivers. Such massive water control projects of India are clearly a threat for a state that lies down of those. Unfortunately, and often ironically, national leaders of our country prefer to negotiate this sensitive matter rather than to make a strong protect of this inhuman and unethical activities. What is more astonishing news is that some time our state policy makers like to keep silent and avoid about it. India is always ready to controlling nature to serve economic development rather than addressing issues of trans-boundary and socio-environmental responsibilities. In fact, Indian plan to divert the water of Frontier Rivers is increasing at an alarming rate for Bangladesh. Here one thing is mentionable that is this types of project even harmful for India also. And peoples of north western state of India are in against of such harmful and high ambitious unnecessary project. Some time they also make a protest against it. Recently China and India are going to establish a large dam at the up Stream of Brahmaputra River. It would impair Indias own plan to link approximately thirty of its own rivers, a project that is bound to affect the downstream riparian state of Bangladesh. As a result drastic fall in the water flow of Teesta during the lean season, especially in February and March will occur in more frequent and will seriously hampers irrigation in Bangladesh. Such international trans-boundary river development projects raise many important issues. They never consider the impact that will impose upon the down stream part like Bangladesh. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14614 J. Sci. Foundation, 8(1&2): 1-12, June-December 2010